Digital Monopoly and Threats to Fair Competition : an Analysis of Antitrust Law in the Platform Ecosystem - Polontoh, Herry M (Ipso Jure, 2025)
The rapid expansion of the digital economy has given birth to a new market structure characterized by the dominance of data-based technology platforms, algorithms, and strong network effects, thus potentially giving rise to a form of digital monopoly that threatens healthy business competition. This study aims to analyze the phenomenon of digital monopoly through the perspective of Indonesian antitrust law, especially based on Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition. The research method used is normative juridical with a normative, conceptual, and analytical approach to practices and literature related to digital business competition law enforcement. The results of the discussion show that national anti-competition legal instruments face normative and technical challenges in reaching out to practices of abuse of dominant positions in the platform ecosystem, such as self-preferencing, digital bundling, and algorithmic-based market locking that are not explicitly covered in the classic indicators of market share and price. The lack of transparency of the system and the cross-border character of the global platform complicate ICC's supervisory capacity in enforcing the rules effectively. Therefore, this study emphasizes the urgency of reformulating an antitrust regulatory approach that is more adaptive to the reality of the digital economy, both through the redefinition of the concept of market power, strengthening enforcement jurisdiction, and the adoption of global principles that emphasize algorithmic transparency and fairness of access for all business actors.